The Effect of Discipline and Work Motivation on Employee Performance at PT Yala Kharisma Shipping, Palembang - Hutagalung , Soly Deo Glorya (Maneggio, 2024)
This study aims to explore the impact of work discipline and work motivation on employee performance at PT Yala Kharisma Shipping Palembang Branch. Data was collected through observation and distributing questionnaires to 40 respondents. Data analysis used multiple linear regression methods. The results of the analysis show that individually, both work discipline and work motivation have a significant influence on employee performance. In addition, together, the two factors also have a significant effect on employee performance. This research provides implications for PT Yala Kharisma Shipping Palembang Branch, that to improve employee performance, companies must pay attention to both work discipline and work motivation.